Dynamic hysteresis scaling in BaTiO3 bulk ceramics - Wongdamnern N. (2014)
The scaling behavior of the dynamic hysteresis of ferroelectric BaTiO 3 bulk ceramics was investigated. Two sets of the scaling relation of hysteresis area against frequency f and field amplitude E0 were clearly established. Approximately, above the coercive field, the scaling took a form of ∝ f-0.23 E00.87. On the other hand, the scaling in the form of ∝ f-0.36 E03.64 was obtained under a sub-coercive field condition. While these scaling relations were generally comparable to previously reported ones, it was found that the f- and E0 exponents clearly depended on E0 and f, respectively. © (2010) Trans Tech Publications.